Impact of Urduised English on Pakistani English Fiction - Sajid Ali, Sajid Ahmad (Journal of Research in Humanities, 2023)
The present work studies the use of Urduised words in the Pakistani English fiction. The present study is a corpus-based study and investigates the influence created through the Urduised words used in the Pakistani English drawing on the data from Pakistani English Fiction corpus (PEF) consisting of one million words . The influence of Urdu through Code- switching has resulted in a lot of innovations at the lexical level in the Pakistani English. The data analysis reveals that Pakistani English shows distinct impact of its indigenous culture through the usage of dynamic lexis steeped in Pakistani culture. The frequent use of Urduised words in Pakistani English Fiction at the lexical level is the distinct feature of Pakistani English and strengthens the fact that Pakistani English being an independent variety has bridged the process of localization and represents independent linguistic norms of its own.